Antihypercholesterolemic Activity of Ethanol Extract from Manilkara kauki Leaves: In Vitro and In Silico Studies - Meilasari, Renita; Tukiran, Tukiran (Indonesian Journal of Chemistry, 2026)
Current food consumption patterns are a significant concern in the field of health. For example, the habit of consuming high-calorie, high-saturated-fat, and high-sugar junk food contributes to various health problems. Fat, as a molecule required by the body as a source of energy, has adverse effects if its levels exceed the amount needed by the body. One of these effects is an increase in cholesterol levels, a condition known as hypercholesterolemia. Manilkara kauki is a plant that has the potential as an antihypercholesterolemic agent. The objective of this study is to evaluate their antihypercholesterolemic activity both in vitro, using the Liebermann-Burchard method, and in silico, by assessing the inhibition of the HMG-CoA reductase enzyme (PDB ID: 1HW9), which plays a key role in cholesterol synthesis. The antihypercholesterolemic activity assessed via the Liebermann-Burchard assay revealed that the ethanol extract exhibited significant activity, with an IC50 value of 108.91 ppm. Furthermore, LC-MS analysis identified 117 compounds in the extract, which were subjected to molecular docking studies. Three flavonoid compounds, lanaroflavone (−8.69 kcal/mol), sequoiaflavone (−9.28 kcal/mol), and sumaflavone (−8.55 kcal/mol), demonstrated higher binding affinities to HMG-CoA reductase than the positive control, simvastatin (−8.53 kcal/mol).